HADIS PALSU DAN HUKUM MERIWAYATKANNYA - Sati, Ali (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2018)
As a narrator (al-râwî), there are some stipulations thosse be must be owned. One of them is the justice (al-‘adâlah). The justice or impartiality is a quality that was settled in the soul motivates someone to be fear of God and keeps his Manliness. It’s one of the quality that must be owned by a narrator for his report receivable. The narrate will be not receiv without the justice quality and even the tradition that he narrates will not be done. There are two ways how to know the justice quality; the famous (al-masyhûrah) and the testimony (tazkiyah). The famous, it means as someone to be known arround the narrator of tradition. And the testimony is one’s or groups aknowlegement in knowledge of tradition departemen. Since in the middle of the first century of the Hejira, hadîth start to be smeared by various forgery. Generally, forgery of the hadîth effecct of attitude of fanatis group wich have get conservative level, political groupgoodness and also religious stream. Besides, there is also among muslem scholar owning the target of goodness. But, they were exactly trapped in impact which charming religion. Faktor of external have influence in forgery many hadîth, like Isrâ’liyyat hadîth.            One of the instrumentto check is the sciense of ta’dîl and jarh. This science concerning evaluationtoall person of the narrator an hadîth. Study about of false hadîth represent central issue theme which told in this paper. From study in the some forum (majlis) which have to be expressed by, that there is over there some hadîth the assumed as false hadîth that unknown of the refrence or narrator. For ekample from fact of matn which has not have the refrence or source, was such as those which told like: I’mal li dunyaka kaanaka ta’îsyu abada, wa ‘mal li âkhiratika kaannaka tamûtu ghada